The Youth Experience Gap: Explaining National Differences in the School-to-Work Transition - Pastore, Francesco (Springer, 2015)
This work points to the youth experience gap as a key concept to explain the meager employment opportunities and earnings many young people face.The transition from education to work remains a long dark tunnel around the world. However, this book shows that there are striking differences between countries: in Germany, the young people of today are no worse off than their adult counterparts, while in Southern European and Eastern European countries they fare 3 through 4 times worse.